Efficiency, Finance, and Varieties of Industrial Policy. - Noman, Akbar (Columbia University Press, 2016)
Industrial policy, once relegated to resource allocation, technological improvements, and the modernization of industries, should be treated as a serious component of sustainability and developmental economics. A rich set of complimentary institutions, shared behavioral norms, and public policies have sustained economic growth from Britain's industrial revolution onwards. This volume revisits the role of industrial policy in the success of these strategies and what it can offer developed and developing economies today. Featuring essays from experts invested in the expansion of industrial polic.